2004
DOI: 10.2320/matertrans.45.2650
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zinc Sulfide Nanocrystals and Fabrication of Nanocrystal Superlattice

Abstract: We report synthesis of zinc sulfide nanocrystals (NCs) via formation of polymetallic thiolate cages. Nearly monodisperse ZnS NCs with size ranging from 2.2 to 7 nm were obtained by thermolysis of S-Zn-dodecanethiol precursors. The electron diffraction pattern of zinc sulfide NCs indicates that precipitates are wurtzite or mixture of wurtzite and zincblende. TEM observation and UV-vis spectra reveal that the growth rate of ZnS NCs considerably depends on the annealing temperature. UV-vis spectra of ZnS NCs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The materials exhibit a direct band gap with values of 1.74, 3.5 and 2.2 eV for copper sulfide, manganese sulfide and the copper sulfide – manganese sulfide particles, respectively. The bulk band gap of copper sulfide ranges from 1.2 to 2.0 eV depending on composition,, but nanoparticle samples of djurleite (Cu 1.94 S) and anilite (Cu 1.75 S) possess band gap values of 1.73 and 1.70 eV respectively, while manganese sulfide is about 3.8 eV, which matches closely with the values measured for the nanoparticles here. The band gap for the copper sulfide‐manganese sulfide particles is intermediate that of the pure materials, supporting the formation of phase segregated heterostructured particles.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The materials exhibit a direct band gap with values of 1.74, 3.5 and 2.2 eV for copper sulfide, manganese sulfide and the copper sulfide – manganese sulfide particles, respectively. The bulk band gap of copper sulfide ranges from 1.2 to 2.0 eV depending on composition,, but nanoparticle samples of djurleite (Cu 1.94 S) and anilite (Cu 1.75 S) possess band gap values of 1.73 and 1.70 eV respectively, while manganese sulfide is about 3.8 eV, which matches closely with the values measured for the nanoparticles here. The band gap for the copper sulfide‐manganese sulfide particles is intermediate that of the pure materials, supporting the formation of phase segregated heterostructured particles.…”
Section: Resultssupporting
confidence: 85%
“…In this experimental approach to forming copper sulfide – manganese sulfide heterostructured particles, the copper sulfide disks are formed first, then manganese precursor is added to initiate manganese sulfide growth on the pre‐formed copper sulfide seeds. The formation of both materials is driven by thermolysis, which is a decomposition facilitated by the catalytic cleavage of the sulfur alkane bond in the alkanethiol molecules used in the synthesis . In this case, the manganese sulfide grows on only one face of the copper sulfide disk, because the disk is anisotropic with one of the broad 001 faces being cationic and the other anionic ,.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colloidal binary copper chalcogenide (Cu 2− x A; A=S, Se, and Te) NCs have attracted increasing attention over the last decade, because their properties make them interesting materials for implementation into several applications, such as solution‐processable photovoltaic and nanoplasmonic devices, photocatalysis, photothermal therapy, and biomedical sensing . Some of these applications will be addressed in more detail in Section 2.4.…”
Section: Binary Copper Chalcogenidesmentioning
confidence: 99%
“…Cabot and co‐workers have proposed an oriented attachment pathway through which hexagonal nanodisks form hexagonal Cu 2− x S bifrustums and eventually hexagonal bipyramids . Other groups have presented evidence that Cu thiolate lamellar complexes act as both Cu precursors and shape‐templating agents . Recent work has demonstrated that the crystallographic phase and composition of Cu 2− x S NCs (see Section 2.1) can be controlled by proper choice of reaction parameters (namely, temperature, molar ratio of Cu/S, and volume ratio between the noncoordinating solvent 1‐octadecene and the ligand oleylamine) .…”
Section: Binary Copper Chalcogenidesmentioning
confidence: 99%